Competence of Entrants and Accounts on the Implementation of Senior High School Pre-Baccalaureate Maritime Program in Negros Occidental - Batalla, Edison T (Future Science / FSH-PH Publications, 2023)
The Philippines is one of the single biggest nationality blocs in the maritime and shipping industries; thus, the country's efforts to improve the Maritime Program in secondary and tertiary education are highly significant. This study aimed to determine the level of competence of Maritime Senior High School students and gather accounts of implementing the maritime program in the basic education system in Negros Occidental. It adopted the mixed-methods sequential explanatory design. The paper used mean, standard deviation, and Mann-Whitney for comparing differences between two independent groups for the statistical treatment analysis of the quantitative data. Coding and identifying common themes, patterns, and responses were used in the thematic analysis of the descriptive information provided by the interviewees. The findings revealed that the competence of the SHS students in the pre-baccalaureate maritime program was at the skill level in terms of introduction to maritime careers and introduction to marine transportation and engineering, and at the leadership level in terms of introduction to maritime safety, irrespective of the school enrolled and preferred program. The development of the quality system and support, execution of the curriculum, administration of assessments, and sustained and continuous pursuit of excellence that comprise the ideal practices of the school explained the current findings. Laying the foundation (PSG), Embedding the PSG into the school norms and practices, acting on or carrying out the program, and Determining Outcomes are the four steps that make up the new paradigm for conducting pre-baccalaureate maritime programs known as LEAD.